Deep X-ray observations of the young high-magnetic-field radio pulsar J1119-6127 and supernova remnant G292.2-0.5 - Ng, C.; Kaspi, V.; Ho, W.; Weltevrede, P.; Bogdanov, S.; Shannon, Ryan; Gonzalez, M. (Institute of Physics Publishing, 2012)
High-magnetic-field radio pulsars are important transition objects for understanding the connection between magnetars and conventional radio pulsars. We present a detailed study of the young radio pulsar J1119-6127, which has a characteristic age of 1900 yr and a spin-down-inferred magnetic field of 4.1 × 1013 G, and its associated supernova remnant G292.2-0.5, using deep XMM-Newton and Chandra X-ray Observatory exposures of over 120 ks from each telescope. The pulsar emission shows strong modulation below 2.5 keV with a single-peaked profile and a large pulsed fraction of 0.48 ± 0.12. Employing a magnetic, partially ionized hydrogen atmosphere model, we find that the observed pulse profile can be produced by a single hot spot of temperature 0.13 keV covering about one-third of the stellar surface, and we place an upper limit of 0.08 keV for an antipodal hot spot with the same area. The non-uniform surface temperature distribution could be the result of anisotropic heat conduction under a strong magnetic field, and a single-peaked profile seems common among high-B radio pulsars. For the associated remnant G292.2-0.5, its large diameter could be attributed to fast expansion in a low-density wind cavity, likely formed by a Wolf-Rayet progenitor, similar to two other high-B radio pulsars.